The Assessment Of Nurses' Knowledge And Attitude Towards Islamic Commandments In Tehran University Of Medical Sciences (TUMS) Hospitals In 2014 - Nikzad Eisazadeh; Khorshid Vaskoei Eshkevari; Jayran Zebardast; Mohammad Malek Mohamadi; Samira Shasty (Tehran University of Medical Sciences, 2015)
Background and Aim: Nurses' knowledge and awareness about religious orders is undoubtedly so important in their relationship with patients in hospitals. So, the aim of this study is to compare the knowledge and attitude of nurses before and after their participation in religious orders workshop. Materials and Methods: In this cross-sectional study, religious knowledge and attitude of 480 nurses working in the hospitals of Tehran University of Medical Sciences (TUMS) were evaluated. The research tool was a questionnaire and such factors as nurses' age, sex, educational level, and type of employment were considered. The data were collected by a questionnaire and analyzed by SPSS software version 19. Results: Nurses demonstrated a higher level of knowledge and attitude in hospitals where Islamic orders workshop was held than the ones in other hospitals. In total, there was no significant difference among nurses regarding their age, sex, educational level, and type of employment however, nurses working in surgical wards and those with a postgraduate degree showed a higher level of knowledge and attitude than others. Conclusion: It is necessary to provide nurses with knowledge about religious orders because such knowledge may increase patients' satisfaction with the care they receive.